Creation of Vlada Radović, Savo Rakočević, Vuk Filipović (Baština, 2024)
TheworkpresentsprominentartistsinKosovoandMetohija–VladaRadović, SavoRakočević, Vuk Filipović. By examining the creativity of Vlado Radović, we can see that he visibly markedthe emergence and development of contemporary Serbian fine arts and education in Kosovo and Metohija.  Savo Rakočević,today one of the most famous contemporary Serbian painters, also achieved his creative beginnings in Kosovo and Metohija. Vuk Filipovic was a prominent university professor and writer, but he also dedicated part of his creativity to painting.
Keywords: KosovoandMetohija, contemporarySerbianpainting, VladaRadović, SavoRakočević, VukFilipović